1976
DOI: 10.1002/hlca.19760590807
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal Complexes with Bidentate Ligands Spanning trans‐Positions. II. Preparation and properties of complexes trans‐[MX2(1)] (M = Ni, Pd and Pt; X = Cl, Br and I; 1 = 2, 11‐Bis(diphenylphosphinomethyl)benzo[c]phenanthrene)

Abstract: It is shown that the ligand 2,11‐bis(diphenylphosphinomethyl)benzo[c]phenanthrene (1) reacts with nickel(II), palladium(II) and platinum(II) substrates giving either exclusively, or predominantly, mononuclear complexes of the type trans‐[MX2(1)] in which the organic ligand spans trans‐positions. It is further shown that the spectroscopic properties which are mainly associated with metal and donor atoms in complexes of this type are closely related to those of the corresponding square planar complexes of the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…data for the complexes [MX (l)] are shown in Table 5 . These spectra were similar in general appearance to those previously reported for the complexes truns-[MX2(1)] (M = Ni, Pd, P t ; X = halide) [19], showing a complex multiplet of aromatic resonances between ca. 7 and 8 ppm, a separate resonance to low field of the main aromatic multiplet arising from the protons in the 1 and 12 positions of the benzo[c]phenanthrene ring and a resonance in the region 3.5-5.0 ppm due to the methylenic protons.…”
Section: B)supporting
confidence: 87%
See 1 more Smart Citation
“…data for the complexes [MX (l)] are shown in Table 5 . These spectra were similar in general appearance to those previously reported for the complexes truns-[MX2(1)] (M = Ni, Pd, P t ; X = halide) [19], showing a complex multiplet of aromatic resonances between ca. 7 and 8 ppm, a separate resonance to low field of the main aromatic multiplet arising from the protons in the 1 and 12 positions of the benzo[c]phenanthrene ring and a resonance in the region 3.5-5.0 ppm due to the methylenic protons.…”
Section: B)supporting
confidence: 87%
“…L4 linear arrangement of metal and pliospliorus atoms, as occuring in 2, is present in complexes [MXz(l)] (M = Ni, Pd and P t ; X =: halide) [19]. Tliere is also evidence 191 suggesting that the comparatively bulky and rigid backbone of ligand 1 renders it far less prone to form diphosphine bridged oligomers tlian are analogous diphosphines with more flexible backbones.…”
Section: )mentioning
confidence: 99%
“…Interatomic distances and interbond angles are given in Table I. 2) 111.0(6) Y-CILO (3) 112.3(7) O( I)-C1-0 (2) 106.7(6) O( 1)-C1-0 (3) 105.4(6) 0 (2)-C1-0(3) 11 1.1 (5) ") Y is the anion, or atom of the anion, bonded to Ag. [7].…”
Section: Resultsmentioning
confidence: 99%
“…-Three-coordinate complexes of Ag(1) with tertiary phosphine ligands normally have trigonal micro-geometry about the metal atom. As the ligand 2,11-bis(diphenylphosphinomethyl)benzo[c]phenanthrene (la) has been shown to prefer spanning trans-positions in square-planar and octahedral complexes [2], it was expected that its complexes with Ag(1) would exhibit considerable distorsion from 120" angles. Indeed, crystallographic studies of the complexes [M(la)Cl] (M = Cu(I), Ag(1) and Au(1)) have shown that although the metal atoms are three-coordinate, the P-M-P angles are 132, 141 and 176", respectively [3].…”
mentioning
confidence: 99%
“…In fact the exhaustive studies performed by Venanzi and co-workers resulted in a series of 19 papers in Helvetica Chimica Acta related to the characterization and reactivity of its derivatives [5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]! Numerous complexes with different coordination numbers and geometries have been synthesized and the structure of many of them has been elucidated by means of X-ray diffraction ( Table 1).…”
Section: General Description Of the Known Ligands: Main Coordination mentioning
confidence: 99%